The function to convert Fahrenheit to Celsius is °C = (°F) =

The inverse function will

9

convert Celsius to Fahrenheit. What is the inverse function? Complete the explanation of how

determining this inverse is different than determining the previous inverses.

The inverse function is °F = -(°C)=

The F and °C (select) V need to be switched like the x and y did in the previous functions.

(select) degree measures, and because of the real-world relationship, switching them

(select) ✓ make sense.

Answer:

**Answer:**

**Step-by-step explanation:**

**Given**

**Required**

Determine the inverse function

**Make F the subject of formula:**

**Multiply through by 9**

**Add 32 to both sides**

**Divide through by 5**

Answer:

The **inverse function** is °F = (9/5 * °C) + 32.

To determine this inverse function, we first need to understand that it's the reverse conversion from Celsius to **Fahrenheit**. In the original conversion from Fahrenheit to Celsius, we subtracted 32 from the Fahrenheit temperature and then divided the result by 9/5 (or 1.8).

To find the inverse, we need to do the opposite operations in reverse order. First, we need to undo the **division **by 1.8, which is equivalent to multiplying by 5/9. Then, we need to undo the subtraction of 32 by adding 32 to the result.

This process is different from determining previous inverses because it involves reversing the operations in the opposite order and with different constants (5/9 and 32) compared to the original function.

The F and °C variables need to be switched in the inverse function because we are now going from Celsius to Fahrenheit, and the relationship between these temperature scales requires different mathematical **operations**.

Switching them makes sense because it aligns with the real-world relationship between the two temperature scales and ensures that the inverse function correctly converts from Celsius to Fahrenheit

for such more questions on **Inverse function **

#SPJ3

Find the measure of the numbered angle

10x-4=-4+10x One Solution, No Solution, Infinitely Many Solutions

Help please =) I need to get this right so I can move on in my lesson things

( -7v 4 - 5v ) - ( -5v 3 - 2v ) + ( -7v - 6v 4 - 4v 3 ) simplified

711.9 divided by 8.4 show work?

10x-4=-4+10x One Solution, No Solution, Infinitely Many Solutions

Help please =) I need to get this right so I can move on in my lesson things

( -7v 4 - 5v ) - ( -5v 3 - 2v ) + ( -7v - 6v 4 - 4v 3 ) simplified

711.9 divided by 8.4 show work?

Answer:

1.646×10¹¹ km³.

Step-by-step explanation:

From the question given, we obtained the following information:

Radius (r) = 3400 km

Volume (V) =.?

The shape of a planet is spherical in nature. Thus, we shall apply the formula for calculating the volume of a sphere to obtain the volume of Planet Mar as illustrated below:

Radius (r) = 3400 km

Pi (π) = 3.14

Volume (V) =.?

Volume of a sphere = 4/3 πr³

V = 4/3 × 3.14 × (3400)³

V = 4/3 × 3.14 × 3.9304×10¹⁰

V = 1.646×10¹¹ km³

From the calculations made above, the volume of Planet Mar is 1.646×10¹¹ km³

O A. 4x-3

O B. 3x - 1

C. 7x-1

O D. 7x-3

SUBM

The solution is : If f(x) = 5x – 2 and g(x) = 2x + 1, then the** value** of (f+g)(x) is : 7x-1.

**Function**, in mathematics, an expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable.

here, we have,

given that,

If f(x) = 5x – 2 and g(x) = 2x + 1,

now, we have to find (f+g)(x).

so, we have,

f(x) = 5x – 2

and g(x) = 2x + 1

now,

(f+g)(x)

=f(x)+g(x)

=5x-2+(2x+1)

=5x-2+2x+1

=7x-1

Hence, The solution is : If f(x) = 5x – 2 and g(x) = 2x + 1, then the** value** of (f+g)(x) is : 7x-1.

To learn more on **function** click:

#SPJ7

**Answer:**

7x-1

**Step-by-step explanation:**

- f(x)+g(x)
- 5x-2+(2x+1)
- 5x-2+2x+1
- 7x-1

Best answer gets brainliest.

**Answer:**

no x=4.5

**Step-by-step explanation:**

**Answer:**

y = - 4.5

**Step-by-step explanation:**

given the equation

- 3 = 15 + 4y ( **subtract** 15 from both sides )

- 3 - 15 = 15 - 15 + 4y ( **simplify** both sides )

- 18 = 4y ( **divide** both sides by 4 )

= y , that is

- 4.5 = y

**Answer:**

**x = - 6**

**Step-by-step explanation:**

**Let x b number, according to instructions´ we must**

**1.-Multiply by 4**

**2.-Subtract 6**

**3.-Divide by 2**

**4.-Arturo says his new number - 15**

**4,.Which one was the original number ??**

**The maths expression for that is :**

**(4*x - 6 ) / 2 = - 15**

**we solve for x**

** 4x - 6 = - 30**

**4x = - 24**

**x = - 6**

To find Arturo's **starting **number, reverse the given steps: divide by 2, add 6, then multiply by 4.

To find Arturo's starting number, we need to reverse the steps Savanna provided. Let's go through the steps backwards:

**Arturo's**number after dividing by 2 is -15 * 2 = -30.- Arturo's number after adding 6 is -30 + 6 = -24.
- Arturo's number after multiplying by 4 is -24 / 4 = -6.

Therefore, Arturo started with the number -6.

#SPJ3

The average height of the 10 tallest buildings in Los Angeles is than the average height of the tallest buildings in San Francisco. The mean absolute deviation for the 10 tallest buildings in San Francisco is

The answer:

**Answer with explanation:**

Average Height of tallest Building in San Francisco

Average Height of tallest Building in Los Angeles

→→Difference between Height of tallest Building in Los Angeles and Height of tallest Building in San Francisco

=233.9-197.8

=36.1

⇒The average height of the 10 tallest buildings in Los Angeles is** 36.1 more **than the average height of the tallest buildings in San Francisco.

**⇒Part B**

**Mean absolute deviation for the 10 tallest buildings in San Francisco**

|260-197.8|=62.2

|237-197.8|=39.2

|212-197.8|=14.2

|197 -197.8|= 0.8

|184 -197.8|=13.8

|183-197.8|=14.8

|183-197.8|= 14.8

|175-197.8|=22.8

|174-197.8|=23.8

|173 -197.8|=24.8

**Average of these numbers**

**Mean absolute deviation=23.12**

Answer:

1st -36.1 meters or more

2nd -23.12

Step-by-step explanation: